Splenic infarction following recurrent torsion of a wandering spleen: A case report - Mohammad Tareq Rahimi; Abdul Jamil Rasooli; Soghra Khaliqi; Nawaz Sharif Kashaf; Palwasha Wardak Mohtasebzada; Roohullah Hares (Elsevier, 2024)
Background: Wandering spleen (WS) is a rare condition characterized by hypermobility of the spleen due to maldevelopment or absence of the ligaments that hold it in its normal location. Splenic infarction following torsion of a wandering spleen is a rare cause of acute abdomen in children and can be difficult to diagnose, especially at secondary healthcare facilities. Case presentation: A 10-year-old girl presented to our clinic with a two-week history of abdominal pain, fever and vomiting. On physical examination she was pale, cachectic and dysmorphic. Painful splenomegaly was noted on palpation. Inflammatory markers were elevated (CRP: 26.7 mg/L; WBC: 20.4 x 109/L). A contrast-enhanced CT of the abdomen revealed splenomegaly with complete splenic infarction due to torsion of the splenic pedicle, consistent with a wandering spleen. The patient underwent an emergent laparotomy through a left subcostal incision. A markedly enlarged spleen was found, with its pedicle completely torsed. The spleen had no attachments to the abdominal wall or diaphragm and appeared non vital. We proceeded with a complete splenectomy. The patient recovered well and was discharged in stable condition on the fifth postoperative day. At 6 months of follow up, she has had no recurrent episodes of abdominal pain. Conclusion: While torsion of a WS is a rare condition, it must be included in the differential diagnosis of children with abdominal pain of unknown etiology.